Ragam Jenis Tumbuhan Obat dan Pemanfaatannya dari Hutan Adat Lubuk Tinting dan Maliki Desa Pungut Hilir Kecamatan Air Hangat Timur Kabupaten Kerinci: Different Types Of Medicine Plants And Its Utilization From Lubuk Tinting And Maliki Traditional Forests, Pungut Hilir Village, East Warm Water District, Kerinci Regency - Nursanti, Nursanti; Adriadi, Ade Adriadi; Mauluddin, Muhammad (Biospecies, 2023)
Medicinal plants are all plant species that produce one or many active components that are used as ingredients for health treatment or all types of plants that are believed to have medicinal properties. One of them is still used by the community around the Lubuk Tinting and Maliki Traditional Forests in Pungut Hilir Village. This study aims to determine the various types of medicinal plants found in the Lubuk Tinting and Maliki Traditional Forests, Pungu Hilir Village, Air Warm East District. The results showed that 43 plant species were found with 30 families. Based on the understorey, seedlings, and saplings. Some families with the highest number of species include Rubiaceae, Lauraceae, Araceae, Arecaceae, Euphorbiaceae, Fabaceae, and Urticacaeae. In the vegetation analysis plot, 43 plant species were found, including 42 plant species with 30 families identified as potential medicinal plants used by ethnic groups throughout the world. In addition, 25 plant species with 18 families with medicinal potential were used by the community from the Lubuk Tinting and Maliki customary forest areas, both in the vegetation analysis plot and outside the vegetation analysis plot. The plants found in the vegetation analysis plot were 10 plant species, while outside the vegetation analysis plot 15 plant species were found. The percentage of organs used by the community around the Lubuk Tinting and Maliki Indigenous Forests as medicine was dominated by 44% (11 species). While the percentage of medicinal plants processing methods is often done by boiling 42% (11 species). The percentage of how to use medicinal plants is mostly done by smearing 37% (10 species). Keywords: Variety of Species, Utilization, Medicinal Plants, Lubuk Tinting, and Maliki Traditional Forests. Â  Abstrak Tumbuhan obat merupakan seluruh spesies tumbuhan yang menghasilkan satu atau banyak komponen aktif yang digunakan sebagai bahan pengobatan kesehatan. Salah satunya masih dimanfaatkan oleh masyarakat Desa Pungut Hilir. Penelitian ini bertujuan untuk mengetahui ragam jenis tumbuhan obat yang terdapat pada Hutan Adat Lubuk Tinting dan Maliki Desa Pungut Hilir Kecamatan Air Hangat Timur. Hasil penelitian menunjukkan ditemukan 43 spesies tumbuhan dengan 30 famili. Berdasarkan meliputi tumbuhan bawah, semai, dan pancang. Beberapa famili dengan jumlah jenis tertinggi antara lain Rubiaceae, Lauraceae, Araceae, Arecaceae, Euphorbiaceae, Fabaceae, Urticacaeae. Pada petak analisis vegetasi ditemukan 43 spesies tumbuhan diantaranya 42 spesies tumbuhan dengan 30 famili teridentifikasi sebagai tumbuhan berpotensi obat. Selain itu ditemukan 25 spesies tumbuhan dengan 18 famili, berpotensi obat yang dimanfaatkan oleh masyarakat dari kawasan Hutan Adat Lubuk Tinting dan Maliki, baik yang terdapat pada petak analisis vegetasi maupun diluar petak analisis vegetasi. Adapun persentase organ tumbuhan yang dimanfaatkan oleh masyarakat disekitar Hutan Adat Lubuk Tinting dan Maliki sebagai obat didominasi daun 44% (11 spesies). Sedangkan cara pengolahan tumbuhan obat sering dilakukan dengan cara direbus 42% (11 spesies), cara pemakaian sering dilakukan dioles 37% (10 spesies). Kata kunci: Ragam Jenis, Pemanfaatan, Tumbuhan Obat, Hutan Adat Lubuk Tinting dan Maliki